There are two sides to every story: implications of asymmetry on breast support requirements for sports bra manufacturers. Issue 7 (3rd October 2021) - Exell, Timothy A.; Milligan, Alexandra; Burbage, Jenny; Risius, Debbie; Sanchez, Amy; Horler, Brogan; Mills, Chris; Wakefield-Scurr, Joanna
ABSTRACT: This study aimed to investigate: (1) the prevalence and magnitude of breast movement asymmetry, (2) the interaction between static and dynamic breast asymmetry and (3) the influence of sports bras on breast asymmetry during running. Position data were collected from 167 females whilst treadmill running and then a sub-group of 12 participants in different bra conditions. Breast movement asymmetry existed in 89% of participants, with resultant static breast position asymmetry larger in participants displaying dynamic asymmetry. Asymmetry was most commonly caused (60% to 75%) by greater movement of the left breast. No significant relationships were found between asymmetry and bra size or breast pain. Sports bras reduced asymmetry prevalence from 75% to 33% of participants in the antero-posterior direction but only from 75% to 67% of participants in the infero-superior direction. The magnitude of range-of-motion asymmetry reduced from 67 mm with no bra to between 6 and 64 mm in-bra in the infero-superior direction, with the best performing bra incorporating encapsulating cups and adjustable straps and underband. It is recommended that sports bras allow underband and strap adjustment to facilitate individual breast support and that asymmetry is considered when designing and fitting bras, which could utilise resultant asymmetry measured statically.